30. Quality of Simeulue buffalo spermatozoa after freezing with AndroMed®diluent - Zamma Khasyarif; Dasrul Dasrul; Ginta Riady; Cut Nila Thasmi; Azhar Azhar (Universitas Syiah Kuala, 2019)
The study aims to determine the effect of diluent concentration Adromed® against the quality of spermatozoa of simeulue buffalo following freezing process. This study uses a completely randomized design (CRD) with 3 treatment groups. Group 1 used AndroMed® diluent 15%; Group 2 with AndroMed® 20%; and, Group 3 with AndroMed® 25%. Each group was repeated 3 times. Quality of spermatozoa assessed includes the motility and viability of spermatozoa. The data on the quality results were analyzed by analysis of variance (ANOVA) in one direction followed by Duncant test. The average percentage of motility after freezing were found in the group P1, P2 and P3 respectively is 32.60 ± 3.27 %; 41.69 ± 4.14 % and 47.58 ± 3.11%; spermatozoa viability is 36.56 ± 3.42%; 47.77 ± 4.81 % and 51.38 ± 3.89%. Statistical analysis showed that the concentration of diluent AndroMed® significantly affected (P 0.05) the motility and the percentage of live sperms. The percentage of live sperm motility and the live sperms did not differ significantly between G1 with G2 treatment groups and both are significantly different (P0.05) compared with group G3. AndroMed® concentration affects the quality of simeulue buffalo spermatozoa after freezing. AndroMed® concentration of 20% and 25% were improved the quality of buffalalo spermatozoa following freezing compared with that with AndroMed® 15% .